Clinical Management and Quality of Life in a Patient with Takayasu Arteritis: A Case Report - Todorović, Slađana; Miljković, Dušan; Jovanović, Miloslav (General Practice, 2026)
Introduction: Takayasu arteritis is a chronic, immune-mediated vasculitis affecting large blood vessels. It is reported worldwide, with an annual incidence ranging from 0.3 to 3.4 cases per million people. The disease predominantly affects young women, with the mean age at diagnosis being approximately 33 years. Early recognition and timely diagnosis exert a favorable influence on disease progression, therapeutic outcomes, and overall quality of life.Case Report. The patient presented is a woman with Takayasu arteritis, which she has been suffering from for the past four years. The diagnosis was established based on medical history, clinical examination, laboratory analyses, echography, MSCT, and PET/CT. To assess work capacity as well as physical and mental status, the SF-36 questionnaire was used. The patient has been regularly monitored and is currently in remission from the disease. Results of the SF-36 questionnaire indicate minor physical complaints, while the greatest impact of the disease is observed in the domains of psychological health and social relationships. Family relations remain intact, and the patient is employed, working a four-day workweek. The only factor positively influencing the course of the disease and the patient’s quality of life is disease remission. Conclusion. Takayasu arteritis is a progressive disease with a significant impact on daily functioning. In patients diagnosed at a younger age, remission is more frequently achieved, which—alongside the prevention of complications—represents the most important factor in attaining a good quality of life. Therefore, efforts should be directed toward reducing the time required for establishing the diagnosis and achieving remission in patients who have already been diagnosed.
Keywords: Takayasu arteritis; quality of life; work capacity; remission induction; diagnosis; ultrasonography